Prognostic Value of Gleason Score at Positive Surgical Margin in Prostate Cancer: A Systematic Review and Meta-analysis - Lysenko, Ivan; Mori, Keiichiro; Mostafaei, Hadi; Enikeev, Dmitry V; Karakiewicz, Pierre I; Briganti, Alberto; Quhal, Fahad; Janisch, Florian; Shariat, Shahrokh F (Clinical genitourinary cancer, 2020)
The individual clinical significance of a positive surgical margin (PSM) after radical prostatectomy has remained controversial. Studies have suggested that the Gleason grade (GG) at the PSM could improve predictive accuracy and decision making. Our objective was to systematically review the reported data to determine the effect of the GG at the PSM on the prognosis after radical prostatectomy. A systematic review was conducted by searching MEDLINE/PubMed for studies reported by June 2019 in accordance with the Preferred Reporting Items for Systematic Review statement. The keywords used included prostate cancer, radical prostatectomy, positive surgical margin, Gleason score, and/or Gleason grade. After a systematic literature review, 10 studies were included, comprising 14,108 patients, of whom 2454 (17.4%) had a PSM and 428 (14%) eventually experienced biochemical recurrence (BCR) within a median follow-up of 18 to 156 months. Data on neoadjuvant or adjuvant therapy were not estimable. In a meta-analysis, GG4 at PSM was significantly associated with BCR compared with GG3 (pooled hazard ratio, 1.87; 95% confidence interval, 1.53-2.28; z = 6.16). The Cochrane Q test (χ2 = 5.88; P = .318) and I2 test (I2 = 15.0%) showed that no significant heterogeneity was present. GG4 at a PSM is a feature of biologically and clinically aggressive prostate cancer that is associated with a significant increase risk of BCR. GG at PSM should be recorded in each pathological report. Given this adverse prognostic value patients with GG4 at the PSM should be considered for multimodal therapy such as radiotherapy.
Keywords: Prostatic Neoplasms; Gleason grade; Radical prostatectomy; nádory prostaty; Margins of Excision; Humans; PSM; resekční okraje; Biochemical recurrence; Prostate-Specific Antigen; lidé; Prostatectomy; Neoplasm Grading; Male; prostatický specifický antigen; prognóza; stupeň nádoru; prostatektomie; lokální recidiva nádoru; PCa; mužské pohlaví; Neoplasm Recurrence, Local; Prognosis